Recurrent lumbar disc herniation recurrence after percutaneous endoscopic lumbar discectomy: A case report. Issue 34 (August 2018) - Wang, Yuanyi; Ning, Cong; Xu, Feng; Xiang, Yipeng; Yao, Liyu; Liu, Yadong; Zhang, Wenjing; Huang, Xiuying; Fu, Changfeng
Abstract: Rationale: Lumbar disc herniation (LDH) is a degenerative disease and affects human health. Although percutaneous endoscopic lumbar discectomy (PELD) can redeem the living quality of patient with LDH rapidly, it appears weak to limit the recurrence rate of LDH. Patient concerns: A 52-year-old male suffered lower back pain and lower limb paralysis for 20 years. However, conservative treatment could not relieve above-mentioned symptoms after doing heavy labor. Diagnoses: Computed tomography (CT) revealed a disc fragment had migrated to the inferior edge of the L5 pedicle. Magnetic resonance imaging (MRI) demonstrated a type 2 Modic change (MC) at L5 and spinal canal stenosis at L4-L5. Based on these findings, the patient was diagnosed with L4-L5 disc herniation and secondary lumbar stenosis. Interventions: The patient underwent surgery twice for PELD at L4-L5 in 1 month. Symptoms were not improved effectively until the conventional posterior discectomy with fusion was performed. Outcomes: No signs of recurrence have been detected in 6 months of follow-up, except for mild lower back pain meeting the temperature change. Lessons: Rapid decompression and instant therapeutic effect do not mean extending the indications of PELD. It is unreasonable to revise the recurrent LDH or treat the primary LDH with PELD under inadequate preoperative assessment.